Improving the Calculation of the Efficiency Assessment of Cash Flow Management in High-Tech Industries - Kemenov, Alexey V.; Abalakina, Tatyana V.; Zhukova, Olga I. (Journal of Reviews on Global Economics, 2018)
Relevance: Information about cash flows is always being closely monitored by analysts, business managers and investors. The efficiency of money management determines the quality of the entity as a whole. And his management should use the integrated indicator of the effectiveness of cash flow management in making management decisions. The novelty of the present scientific research is in the following: - the advanced method of calculation of the integral indicator of the efficiency of cash flows management at the high-tech enterprises is proposed, - the appropriate and efficient use of cash flow profitability indicators is identified. Practical usefulness. - It is justified that The Net Present Value (NPV) profitability of net cash flow is the indicator that reflects the efficiency of cash flow management. - The proposed integral indicator of the effectiveness of cash flow management makes it possible to determine the impact of individual factors that influence the formation and use of NPV. - the proposed efficiency assessment for effective cash management will determine the quality of management of activity of the economic entity.